Water column nutrient, chlorophyll and dissolved organic carbon concentrations and dissolved organic matter characteristics in Roskilde Fjord, Denmark - Eero Asmala; Lumi Haraguchi; Stiig Markager; Philippe Massicotte; Bo Riemann; Peter A Staehr; Jacob Carstensen (PANGAEA, 2018)
Anthropogenic nutrient enrichment is changing the structure and the function of coastal ecosystems. These coastal zones are transitions between freshwater and marine systems where multiple biogeochemical processes remove, produce and transform organic matter. The extent to which the coastal zone is merely a conduit for terrestrial (allochthonous) organic matter, versus a distinct source of autochthonous organic matter fueled by eutrophication, is unclear. To address this issue, we characterized the freshwater and marine dissolved organic matter (DOM) pools in an eutrophic estuary with a long water residence time (Roskilde Fjord, Denmark) over an annual cycle. We combined elemental, optical (absorbance and fluorescence) and isotopic analyses to obtain insight about the bulk properties of the DOM pool during this period. We also used sediment traps to analyze the changes related to the exchange of organic matter between the particulate (POM) and dissolved (DOM) fractions. The results showed that labile autochthonous DOM from in situ primary production was rapidly transformed to more recalcitrant DOM that accumulated in the estuary despite continuous exchange with the open sea. Also, parts of the POM pool were degraded rapidly (within 24h) and transformed into the DOM pool. Accumulated DOM was characterized by relatively low molecular size and stable carbon isotopic value, and by high protein-like fluorescence. These results indicate that autotrophic material can be a major source of specific recalcitrant DOM in eutrophic coastal waters, contributing significantly to the flux of organic carbon to the ocean.
Supplement to: Asmala, E et al. (2018): Eutrophication leads to accumulation of recalcitrant autochthonous organic matter in coastal environment. Global Biogeochemical Cycles, 32(11), 1673-1687, https://doi.org/10.1029/2017GB005848